Endometrial immune profiling and precision therapy increase live birth rate after embryo transfer: a randomised controlled trial - Lédée, Nathalie; Petitbarat, Marie; Dray, Geraldine; Chevrier, Lucie; Kazhalawi, Alaa; Rahmati, Mona; Vicaut, Eric; Diallo, Abdourahmane; Cassuto, Nino Guy; Ruoso, Lea; Prat-Ellenberg, Laura (Frontiers in Immunology, 2025)
IntroductionDespite advancements in assisted reproductive treatments, 70% of transferred embryos fail to implant successfully, yielding significant personal and global repercussions. One promising avenue of research is to take into account the individual’s immune uterine profile in order to tailor treatment and optimise outcomes. This randomised controlled trial represents the initial exploration into the consequences of disregarding the state of the uterine immune environment in infertile women embarking on IVF/ICSI.Materials and methodsThis randomised controlled open two-arm trial included IVF patients, with assessment of immune endometrial environment and precision therapy before embryo transfer (ET). 493 patients were enrolled from October 2015 to February2023. Endometrial biopsies were collected during the mid-luteal phase. Endometrial immune profiling involves the analysis of cytokine biomarkers in the endometrium. If an immune endometrial dysregulation was diagnosed, a computerised randomisation assigned patients to either a conventional ET (disregarding the immune profile) or a personalised ET (with a precision therapy adapted to the immune profile). The primary analysis focussed on demonstrating the superiority of precision treatments using the modified intent-to-treat population (mITT), excluding patients without ET. The primary endpoint was the live birth rate (LBR) following the first attempt of ET.ResultsAmong the population, 78% had an endometrial immune dysregulation and were randomised. The mITT analysis showed a significant increase in LBR with precision care compared to conventional care (29.7% vs. 41.4%; OR: 1.68 [1.04-2.73], p=0.036). The positive impact of precision care was particularly noticeable in patients with morphologically suboptimal embryos (LBR: 21.2% vs. 39.6%; OR: 2.12 [1.02-4.41]) or those with a history of two or more failed ET (LBR: 23.4% vs. 48.1%; OR: 3.03 [1.17-7.85]).Limitations and reasons for cautionThe data should be interpreted with caution due to inherent structural limitations of human IVF trials. Generalising and empowering our findings would rely on the replication of controlled trials by independent research teams possibly integrating the usage of optimised embryo quality with PGT-A.ConclusionThe regulation of the endometrial immune environment emerges as one of the leading innovative strategies to facilitate embryo implantation and enhance the overall performance of assisted reproductive therapies (ART). Based on these findings, endometrial immune profiling could become an essential part of routine ART practice.Clinical trial registrationclinicaltrials.gov, identifier NCT02262117.